ANALISIS NILAI KARAKTER PADA LAGU ANAK DALAM BUKU TEMATIK SISWA KELAS V SEKOLAH DASAR - Servista Bukit; Ernawati Ernawati; Rini Ramadhani (Pedir Research Institut, 2023)
The importance of character building for elementary school students encourages teachers to innovate in realizing character education. The focus of this research is to analyze the character values ​​contained in children's songs. As one of the teacher's efforts to shape the character of elementary school students through habituation. This research method uses a qualitative descriptive approach to achieve research focus. The object of this research is a children's song with the title: nenek moyangku, mars hidup sehat, and bintang kecil. Each research object was analyzed to find the character values ​​contained in the song implicitly to be conveyed to children. With the hope that conveying character values ​​in children's songs on a regular basis can provide an understanding of what is good and what is not good for elementary school students to do. The analysis of the research results shows that the character values ​​obtained include: honesty, hard work, responsibility, self-confidence, independence, cooperation, caring, mutual cooperation, and nationalism.